Biomarkers for atopic dermatitis: a systematic review and meta-analysis. Issue 5 (October 2015) - Thijs, Judith; Krastev, Todor; Weidinger, Stephan; Buckens, Constantinus F.; de Bruin-Weller, Marjolein; Bruijnzeel-Koomen, Carla; Flohr, Carsten; Hijnen, DirkJan
Abstract : Purpose of review: A large number of studies investigating the correlation between severity of atopic dermatitis and various biomarkers have been published over the past decades. The aim of this review was to identify, evaluate and synthesize the evidence examining the correlation of biomarkers with disease severity in atopic dermatitis patients, something that has not been performed previously. Recent findings: Three electronic databases were systematically searched and relevant studies were selected for inclusion. A total of 222 articles, reporting on 115 different biomarkers in 30 063 patients, were critically appraised. Studies were divided into two main groups. The first group consisted of longitudinal randomized controlled trials and cohort studies, which reported measurements at multiple time points. The second contained cross-sectional studies that reported only one measurement per patient. Out of 222 articles, 108 articles reported sufficient data for meta-analysis. Only four biomarkers were eligible for meta-analysis in the longitudinal group, and nine in the cross-sectional group. Summary: Serum thymus and activation-regulated chemokine (TARC) was found to be the most reliable biomarker studied, showing pooled correlation coefficients of 0.60 (95% CI 0.48–0.70) and 0.64 (95% CI 0.57–0.70) in longitudinal and cross-sectional studies, respectively. Additional biomarkers that could prove useful but require additional research include serum cutaneous T-cell attracting chemokine (CTACK), sE-selectin, macrophage-derived chemokine (MDC), lactate dehydrogenase (LDH) and interleukin (IL)-18. Abstract : Supplemental Digital Content is available in the text